Effect of Retrograde Autologous Priming on Clinical Outcome of Cardiopulmonary Bypassing on Patients Undergoing Coronary Artery bypass Grafting - Musa Rafiee; Mohammad Zia Toutounchi; Rezvan Yazdani; Nooredin Mohammadi (International Journal of Cardiovascular Practice, 2019)
Introduction: Cardiopulmonary bypass is a standard and low mortality-associated method used across the world. This method allows cardiac surgery to be performed in a bloodless environment. The study aimed to compare Conventional priming and Retrograde autologous prime (RAP) on patients undergoing coronary artery bypass grafting (CABG).Methods: The study population was patients undergoing CABG using cardiopulmonary bypass in Rajaei Hospital, of whom 80 patients were selected by simple random sampling convenience sampling and then were randomly assigned to two groups: Conventional priming and RAP. Demographic information, blood components transfused in the operating room and the intensive care unit, ejection fraction (EF) of left ventricle and changes in blood gases were collect.Results: The mean requirement for red blood cell transfusion bags to the patient during surgery was lower in the RAP group than the conventional priming group (P = 0.002). But the difference after surgery in both groups was not significant statistically (P = 0.2). The difference amount of platelet transfusion during operation the difference was not statistically significant (P = 0.4). The difference postoperative platelet transfusion was not statistically significant (P = 0.7). The fresh frozen plasma transfusion during surgery in the RAP group lower than the usual prime group, but the difference was not statistically significant (P = 0.406). The Fresh frozen plasma (FFP) transfusion after surgery in the two groups was not statistically significant (P = 0.217).Conclusion: RAP is compared with conventional priming a safe and low-cost technique in reducing the priming volume of the CPB system, causes less hemodilution, and reduces the need for intra- and postoperative blood transfusion. Therefore, it is recommended to consider RAP as an effective and low-cost technique of priming Cardiopulmonary bypass circuits.